CHARACTERISTICS OF THE PRACTICE OF PHYSICAL ACTIVITY AND SPORTS IN PRÉ-TEENS IN ARACAJU (Original Portuguese version) - Aragão, Iuri Roseno Matos (2014)
The aim of this study was to identify the characteristics of the physical and / or sporting activities practiced and preferably of pre-teens. This is a cross-sectional, empirical, and descriptive study. The sample consisted of 145 students between 11-14 years old, of both genders. The mean age was 12.72 ± 1.19 years, 66 males (12.59 ± 1.23 years) and 79 females (12.83 ± 1.16 years). The sample was between the 6th and 9th grade year of elementary school. We applied a questionnaire of 12 questions with closed and open questions proposed specific for this study. The main results indicate that boys perform physical and/or sporting activities outside of school for longer time, more days per week and hours per day than girls. The motivation for practice outside of school was because of personal preferences. The subjects remain too long on individual activities like watching TV, using the computer and playing video games, in the detriment of collective activities such as playing with friends, these were the preferences expressed by the group. The school is the preferred location for the practice of physical and/or sporting activities. The Boys preferences were group activities (football) and the girls preferences were individual activities (swimming). Therefore, everyone wants to know and learn other sports, which indicates potential for future interventions.